Species richness and phytogeographic affinities of rattan genus Korthalsia in Malaysia - Azi Azeyanty Jamaludin (Tanjung Malim, 2023)
Species richness and phytogeographic affinities of rattan genus Korthalsia in Malaysia by Azi Azeyanty Jamaludin